High-purity low-resistivity beta-phase silicon carbide material as well as preparation method and application thereof

By extracting silicon and carbon sources from rice husks, combining deionized water and inorganic acid pretreatment, low oxygen charring and alkali aqueous solution treatment, high-purity and low resistivity β-phase silicon carbide materials are prepared, which solves the problem of difficult to prepare high-purity and low resistivity β-phase silicon carbide materials in the prior art, and achieves efficient preparation that meets semiconductor manufacturing requirements.

CN119822843AActive Publication Date: 2025-04-15BEIJING YISHENG PRECISION SEMICON CO LTD

Patent Information

Application Number
CN202510103052.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-15
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

It is difficult to effectively prepare high-purity, low-resistivity β-phase silicon carbide materials in the prior art, especially without adding metal oxide sintering additives, which are difficult to meet the high purity and low resistivity requirements of semiconductor manufacturing.

Method used

Rice husks are used as raw materials for silicon and carbon, and metal elements are removed by pretreatment of deionized water and inorganic acid, and then carbonized in a low oxygen environment, and heated and filtered in a water bath using alkaline aqueous solution, and finally sintered at high temperature and high pressure to prepare a high-purity β-SiC sintered body.

Benefits of technology

The preparation of β-phase silicon carbide materials with high purity (higher than 99.99%) and low resistivity (≤0.5Ω·cm) has been achieved, which meets the requirements of high purity and low resistivity for semiconductor manufacturing, while avoiding the use of toxic and harmful raw materials and chemical reagents, and has the characteristics of environmental protection and sustainable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0005254683740000011
    Figure HDA0005254683740000011
Patent Text Reader

Abstract

The invention relates to the technical field of semiconductor part materials, in particular to a high-purity low-resistivity beta-phase silicon carbide material and a preparation method and application thereof. The method specifically comprises the following steps: soaking washed rice husks in a weakly acidic aqueous solution, boiling the rice husks in an acidic aqueous solution before use, and cleaning and drying the rice husks; carrying out low-temperature carbonization on the dried rice hulls, cooling, and then carrying out ball milling and sieving; further carrying out water-bath heating and stirring with an aqueous alkali solution, and filtering; the filtrate is a silicate aqueous solution B; drying the filter residue D; the filter residues D are subjected to heat preservation, cooling and washing, and rice husk carbon E is obtained and dried; carrying out ball milling on the silicate aqueous solution B and the rice husk carbon E, and drying to constant weight to obtain a loose block F; burning the loose block F to obtain beta-SiC powder; the beta-SiC powder and the superfine silicon carbide powder are mixed and sintered, and the beta-SiC sintered body is obtained. The silicon carbide material prepared by the invention can meet the requirements of high purity and high density required in the semiconductor manufacturing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of semiconductor component materials, and in particular to a high-purity, low-resistivity β-phase silicon carbide material and a preparation method and application thereof. Background Art

[0002] Silicon carbide materials have similar electrical conductivity to silicon and good resistance to ion etching. With the advancement of integrated circuit miniaturization, the demand and importance of etching processes in integrated circuit manufacturing are increasing, and the power and energy of etching plasma continue to increase, especially in capacitively coupled plasma (CCP) etching equipment, which requires higher plasma energy. Therefore, the use rate of semiconductor precision parts made of silicon carbide materials is increasing.

[0003] β-SiC belongs to the cubic system and has a sphalerite crystal structure. It can be synthesized at a temperature below 1700°C, which is much lower than the temperature required in the synthesis of α-SiC. Therefore, the sintering reaction activity in the synthesis of β-SiC is better, the particles are easier to refine and homogenize, and a large number of nano, submicron and micron ultrafine powders can be produced. The C-rich raw materials used to synthesize β-SiC include activated carbon and carbon black; the Si-rich raw materials include Si, SiO2, silane, etc.

[0004] Under the same sintering process, the resistivity of β-SiC powder is always lower than that of α-SiC powder. For silicon carbide materials for semiconductor components that cannot add any metal oxide sintering aids, β-SiC is more suitable for the high purity and low resistivity requirements of some semiconductor components. However, the cost of β-SiC powder is several times that of α-SiC powder, which is a raw material powder with no market and has not been commercially applied in China. The existing rough powder synthesis method cannot meet the high purity requirements of materials in the semiconductor manufacturing environment. In addition, there are many process flows for sintering SiC, involving batching, mixing, granulation, molding, degreasing, and sintering. Impurities may be introduced in each link, making it difficult to maintain the purity of the raw material powder. Finally, in industry, whether it is traditional solid-phase sintering or liquid-phase sintering methods, sintering aids are inevitably added, which makes the purity of the material drop sharply, especially the introduction of metal elements. Parts containing metal impurities are fatal to the environmental impact of wafer manufacturing. Therefore, it is extremely difficult to prepare high-purity, low-resistivity β-phase silicon carbide materials using powder as raw material using traditional industrial sintering methods.

[0005] At present, most processes for preparing silicon carbide powder use a mixture of high-purity silicon powder and high-carbon materials and sinter them under high temperature conditions, which are high temperature, high pressure, and air isolation. Since solid-phase reactions are generally difficult to carry out thoroughly, air oxidation and acid washing are required after the reaction to obtain high-purity SiC powder. There are currently methods for preparing high-purity SiC powder, but there are few methods for preparing high-purity β-SiC powder. Recent purity research has mainly focused on α-SiC powder, the raw material for third-generation semiconductor silicon carbide wafers.

[0006] The related art discloses a method for preparing high-purity silicon carbide raw materials. The obtained silicon carbide powder with a D50 of 50-800μm and a purity of >99.999% is used to produce silicon carbide wafers. The main crystal phase is α phase, which is not suitable for preparing silicon carbide semiconductor components.

[0007] The related technology discloses a method for preparing high-purity silicon carbide ultrafine particles at low temperature and low cost. The waste generated by cutting single crystal silicon rods is processed and used as a high-purity silicon source. The waste is placed in a vacuum sintering furnace and hydrocarbon gas and argon gas are introduced to achieve full carbonization of the silicon powder to obtain high-purity silicon carbide powder. However, the purity value of the silicon carbide powder is not clearly stated.

[0008] The related art also discloses the use of methyldichlorosilane and sodium aluminum tetrahydride to synthesize methylsilane, and the separation and purification technology is used to separate and purify the crude methylsilane produced by the reaction to a 6N level as a raw material for the production of high-purity silicon carbide powder. However, the preparation method and purity of silicon carbide powder are not mentioned.

[0009] In the field of silicon carbide parts for semiconductor equipment, domestic and foreign companies generally use chemical vapor deposition (CVD) for production, and the purity can reach more than 5N to meet the high purity, corrosion resistance, and plasma etching resistance required for semiconductor manufacturing. However, this method not only has toxic raw materials, dangerous reactions, flammable and explosive byproducts, and is difficult to clean the furnace chamber, but also has theoretical limitations in the deposition rate, and cannot react quickly to synthesize silicon carbide materials. Especially for disc-type parts with a thickness of more than 4mm, due to the limitations of the tooling of the supporting substrate, more than two depositions must be performed, otherwise defects will be left on the material, resulting in the product being unusable. In addition, the deposition amount of the disc is large, and the single deposition time is greatly extended compared to the ring-type products, which brings long time, high cost, slow cycle and high risk to the manufacture of silicon carbide materials, which is not convenient for mass production. However, with the continuous improvement of semiconductor processes, the requirements and frequency of use of semiconductor equipment are constantly increasing. Taking silicon carbide electrodes as an example, the diameter of the current international mainstream products has reached more than 480mm, and the thickness is more than 12mm. Considering that the subsequent machining process is subtractive manufacturing, the size specifications of the material are higher.

[0010] Therefore, it is necessary to find a more efficient sintering method to achieve the preparation of high-purity, low-resistivity β-phase silicon carbide materials so that they can simultaneously meet the high purity and low resistivity requirements required for semiconductor manufacturing. Summary of the invention

[0011] The present application provides a high-purity, low-resistivity β-phase silicon carbide material and a preparation method and application thereof.

[0012] The present application provides a method for preparing high-purity, low-resistivity β-phase silicon carbide material by sintering method, and the prepared silicon carbide material can meet the high purity and low resistivity requirements required by the semiconductor manufacturing process.

[0013] The silicon carbide material provided in this application is different from the third-generation semiconductor silicon carbide. It is not a material used to grow wafers to make silicon carbide chips, but a material for equipment parts used in semiconductor manufacturing. The two have different uses, manufacturing processes, microscopic crystal phases, and performance requirements.

[0014] Rice husk is a biomass material rich in silicon and organic carbon, with low cost and great potential. Its composition and structure determine that it can be used to prepare high-quality silicon carbide materials. Rice husk ash has the highest silicon content among agricultural wastes, and silicon exists mainly in an amorphous structure, so it can be used as a silicon source for extraction. The SiO2 aggregates extracted from rice husk ash are easily broken into nano-scale raw material particles, with residual organic components on their surface and high dispersibility, which can give full play to the high activity of nano-scale raw materials, allowing subsequent synthesis reactions to be fully carried out at a lower temperature.

[0015] However, in addition to the carbon and silicon needed to prepare silicon carbide materials, rice husks also contain other metal elements. These metal elements will react with silicon dioxide during the carbonization process of rice husks to form low-melting-point salts that cause the materials to agglomerate. The water-soluble metal elements in rice husks can be removed by pretreating the rice husk raw materials with deionized water immersion. The results show that the removal rate of K elements in rice husks by water pretreatment reached 63%, and the removal rate of overall metal elements was 40%; inorganic acid pretreatment can remove more than 95% of the metal elements in rice husks, greatly ensuring the removal of metal elements in rice husks. In contrast, the effect of organic acid (acetic acid) in removing metal elements in rice husks is less effective.

[0016] In a first aspect, the present application provides a method for preparing a high-purity, low-resistivity β-phase silicon carbide material, using the following technical solution:

[0017] A method for preparing a high-purity, low-resistivity β-phase silicon carbide material, the preparation method specifically comprising the following steps:

[0018] (1) mixing rice husks and water in a volume ratio of 1:(1-5), stirring thoroughly, taking out the upper layer of rice husks and placing them in a weakly acidic aqueous solution for later use; before use, boiling the rice husks in the acidic aqueous solution for 2-5 times, washing, and drying;

[0019] (2) placing the dried rice husk in a low-oxygen environment at 450-600° C. for 1-6 hours, and after cooling, ball milling at a speed of 100-200 r / min for 1-4 hours to obtain carbonized rice husk powder; passing through a 150-300 mesh fine sieve, and retaining the carbonized rice husk powder A on the sieve;

[0020] (3) heating the carbonized rice husk powder A and a 10-50 wt% alkali aqueous solution in a water bath at 90-100° C. with stirring for 2-4 h, and filtering; the resulting filtrate is a silicate aqueous solution B; and drying the resulting filter residue D;

[0021] (4) placing the filter residue D at 600-800° C. in vacuum or under inert gas protection for 1-3 hours, cooling and washing to neutrality to obtain rice husk carbon E, and drying;

[0022] (5) The silicate aqueous solution B and the rice husk carbon E are mixed according to a molar ratio of carbon to silicon of 2.3-2.5, ball-milled at a speed of 100-200 r / min for 1-2 h, and dried to constant weight to obtain a loose block F;

[0023] (6) slowly calcining the loose block F at 1500-1850° C. to obtain β-SiC powder;

[0024] (7) The β-SiC powder is mixed with 1-30 wt.% of ultrafine silicon carbide powder with an average particle size of 10-100 nm, and sintered at 1900-2000° C. and 30-50 MPa to obtain a β-SiC sintered body.

[0025] The β-SiC sintered body has a purity higher than 99.99% and a volume resistivity of 0.5Ω·cm or less.

[0026] Optionally, in step (1), the weakly acidic aqueous solution and the acid in the acidic aqueous solution are inorganic acids.

[0027] Optionally, in step (1), the acid in the weakly acidic aqueous solution and the acid in the acidic aqueous solution is at least one of hydrochloric acid, sulfuric acid, nitric acid and acetic acid.

[0028] Optionally, in step (2), the material of the fine sieve is an organic material and does not contain metal elements.

[0029] Optionally, the fine screen is made of plastic.

[0030] Optionally, in step (3), the alkali in the alkaline aqueous solution is at least one of ammonia water and an organic base, and the purity of the alkali is higher than 99% and does not contain any metal elements.

[0031] Optionally, the alkali in the aqueous alkali solution must contain nitrogen element.

[0032] In a second aspect, the present application provides a high-purity, low-resistivity β-phase silicon carbide material prepared using the above-mentioned preparation method.

[0033] In a third aspect, the present application provides an application of the above-mentioned high-purity, low-resistivity β-phase silicon carbide material as a component material for semiconductor manufacturing.

[0034] In summary, the present application includes at least one of the following beneficial technical effects:

[0035] 1. The present application extracts highly active silicon and carbon sources from rice husks for the synthesis of high-purity β-phase silicon carbide powder. Meanwhile, a sufficient amount of nitrogen is creatively introduced during the powder synthesis reaction process, thereby greatly increasing the doping amount of nitrogen and providing a good doping basis for the preparation of low resistivity required for semiconductor component electrode products.

[0036] 2. This application uses low-cost crop waste as raw material to synthesize high-value-added β-SiC powder at a relatively low temperature, and successfully prepares a high-purity, low-resistivity β-SiC sintered body that can be used as a semiconductor component material.

[0037] 3. This application uses renewable biomass resources as raw materials. Rice husks have the characteristics of zero pollution, wide sources and large reserves. The recycling and reuse of rice husks solves the problem of handling crop waste and realizes the economic benefits of renewable resources.

[0038] 4. In the process of synthesizing β-SiC powder and β-SiC sintered body, no toxic or harmful raw materials and chemical reagents are used, which is environmentally friendly and sustainable. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 These are the XRD test results of the SiC sintered body and SiC powder obtained in Example 1. DETAILED DESCRIPTION

[0040] Before describing the embodiments of the present application in detail, it should be understood that the terms used herein are only used for the purpose of describing specific embodiments. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by ordinary technicians in the field to which the terms belong.

[0041] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.

[0042] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0043] In the present application, the terms "comprise" or "include" are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0044] The present application provides a method for preparing a high-purity, low-resistivity β-phase silicon carbide material. The preparation method specifically comprises the following steps:

[0045] (1) Mix rice husks and water in a volume ratio of 1:(1-5), stir thoroughly, and soak the upper layer of rice husks in a weakly acidic aqueous solution for later use. Before use, boil the rice husks in the acidic aqueous solution for 2-5 times, wash with distilled water, and dry the water. The acid in the weakly acidic aqueous solution and the acidic aqueous solution is at least one of hydrochloric acid, sulfuric acid, nitric acid, and acetic acid.

[0046] (2) placing the rice husk obtained by drying in step (1) in a heating furnace, keeping it warm in a low-oxygen environment at 450-600° C. for 1-6 hours, taking it out after cooling, placing it in a ball mill and ball milling it at a speed of 100-200 r / min for 1-4 hours to obtain carbonized rice husk powder; passing it through a 150-300 mesh fine sieve, taking the carbonized rice husk powder A under the sieve and setting it aside.

[0047] The fine screen is made of organic material and cannot contain metal elements, and can be made of engineering plastics such as nylon (PA), polyethylene (PE), and polypropylene (PP).

[0048] (3) The carbonized rice husk powder A obtained in step (2) and a 10-50 wt% alkali aqueous solution are heated in a water bath at 90-100° C. with stirring for 2-4 h, and filtered; the obtained filtrate is a silicate aqueous solution B, which is set aside; the obtained filter residue D is dried and set aside.

[0049] The alkali in the aqueous alkali solution is at least one of ammonia water and an organic alkali, the purity of the alkali is higher than 99% and does not contain any metal element. In particular, the aqueous alkali solution must contain nitrogen.

[0050] (4) placing the filter residue D obtained in step (3) in a vacuum furnace, keeping it warm at 600-800° C. in vacuum or under the protection of inert gas for 1-3 h, taking it out after cooling, washing it to neutrality, obtaining rice husk carbon E, and drying it for later use.

[0051] (5) The silicate aqueous solution B obtained in step (3) and the rice husk carbon E obtained in step (4) are mixed according to a molar ratio of carbon to silicon of 2.3-2.5, placed in a ball mill and ball milled at a speed of 100-200 r / min for 1-2 h, taken out and placed in a vacuum oven to dry to constant weight, to obtain a loose block F.

[0052] (6) The loose block F obtained in step (5) is placed in a vacuum furnace and slowly calcined at 1500-1850° C. to obtain β-SiC powder with an average particle diameter of 0.5-20 μm.

[0053] (7) Mixing the β-SiC powder obtained in step (6) with 1-30 wt.% of ultrafine silicon carbide powder with an average particle size of 10-100 nm, sintering in a hot press furnace at 1900-2000° C. and 30-50 MPa to obtain a β-SiC sintered body. The purity of the β-SiC sintered body is higher than 99.99% and the volume resistivity is ≤0.5Ω·cm.

[0054] In addition, nano-scale β-SiC powder can be prepared by combining the sol-gel method with the carbon thermal reduction method. However, the sol-gel method is a liquid phase synthesis method, which is difficult to carry out industrial mass production, and the purity of the reaction product is difficult to control. To obtain high-purity silicon carbide powder, organic raw materials with high purity (5N or above) and no metal impurities are required. The reaction catalysts that may be used in this method include nickel salts, iron salts, etc., and there is a risk of introducing metal elements, which is not suitable for the preparation of semiconductor component materials.

[0055] In addition, although other biomass resources can be used to replace rice husks, such as straw, etc., the rod-shaped crops need to be cut before soaking and removing impurities, and the cutting equipment may involve the introduction of metal impurities.

[0056] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. The embodiments described below are exemplary and are only used to explain the present application, and cannot be interpreted as limiting the present application.

[0057] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0058] The present application is further described in detail below in conjunction with the embodiments and test results.

[0059] Example 1

[0060] This embodiment provides a method for preparing a high-purity, low-resistivity β-phase silicon carbide material.

[0061] The preparation method specifically comprises the following steps:

[0062] (1) Mix rice husks and deionized water in a volume ratio of 1:3, stir thoroughly, take the upper rice husk, and soak it in a weakly acidic hydrochloric acid aqueous solution for later use. Before use, boil the upper rice husk in a dilute hydrochloric acid aqueous solution for 3 times, wash it repeatedly with distilled water, and dry it.

[0063] (2) The rice husk obtained by drying in step (1) is placed in a heating furnace, kept at 500° C. for 4 h in a low oxygen environment, taken out after cooling, and placed in a ball mill at a speed of 150 r / min for 2 h to obtain carbonized rice husk powder; the carbonized rice husk powder A under the sieve is taken out and set aside.

[0064] (3) The carbonized rice husk powder A obtained in step (2) and a 25 wt% ammonia solution are heated in a water bath at 90° C. and stirred for 4 h, and filtered. The filtrate obtained is the silicate aqueous solution B, which is reserved; the filter residue D obtained is dried and reserved.

[0065] (4) The filter residue D obtained in step (3) is placed in a vacuum furnace and kept warm at 700° C. for 2 h. After cooling, the residue is taken out and washed to neutrality to obtain rice husk carbon E, which is then dried for later use.

[0066] (5) The silicate aqueous solution B obtained in step (3) and the rice husk carbon E obtained in step (4) are mixed according to a molar ratio of carbon to silicon of 2.5, placed in a ball mill and ball milled at a speed of 100 r / min for 2 h, taken out and placed in a vacuum oven to dry to constant weight, to obtain a loose block F.

[0067] (6) The loose block F obtained in step (5) is placed in a vacuum furnace and slowly calcined at 1650° C. to obtain β-SiC powder.

[0068] (7) The β-SiC powder obtained in step (6) is mixed with 20 wt.% of silicon carbide powder having an average particle size of 50 nm, and the mixture is placed in a hot press furnace and sintered at 2000°C and 30 MPa to obtain a β-SiC sintered body.

[0069] Example 2

[0070] This embodiment provides a method for preparing a high-purity, low-resistivity β-phase silicon carbide material.

[0071] The preparation method specifically comprises the following steps:

[0072] (1) Mix rice husks and deionized water in a volume ratio of 1:5, stir thoroughly, take the upper rice husk, and soak it in a weakly acidic sulfuric acid aqueous solution for later use. Before use, boil the upper rice husk in a nitric acid aqueous solution twice, wash it repeatedly with distilled water, and dry it.

[0073] (2) The rice husk obtained by drying in step (1) is placed in a heating furnace, kept at 600° C. for 3 h in a low oxygen environment, taken out after cooling, and placed in a ball mill for 4 h at a speed of 100 r / min to obtain carbonized rice husk powder; the carbonized rice husk powder A under the sieve is taken out through a 150-mesh polypropylene (PP) sieve for later use.

[0074] (3) The carbonized rice husk powder A obtained in step (2) and a 30 wt.% polyethyleneimine aqueous solution are heated in a water bath at 90° C. and stirred for 3 h, and the filtrate is filtered to obtain a silicate aqueous solution B for later use, and the filter residue D is dried for later use.

[0075] (4) The filter residue D obtained in step (3) is placed in a vacuum furnace and kept warm at 800° C. for 1.5 h under the protection of an argon atmosphere. After cooling, the residue is taken out and washed until neutral to obtain rice husk carbon E, which is then dried for later use.

[0076] (5) The silicate aqueous solution B obtained in step (4) and the rice husk carbon E obtained in step (4) are mixed according to a molar ratio of carbon to silicon of 2.4, placed in a ball mill and ball milled at a speed of 200 r / min for 1 h, and then taken out and placed in a vacuum oven to dry to constant weight to obtain a loose block F.

[0077] (6) The loose block F obtained in step (5) is placed in a vacuum furnace and slowly calcined at 1700° C. to obtain β-SiC powder.

[0078] (7) The β-SiC powder obtained in step (6) is mixed with 8 wt.% of ultrafine silicon carbide powder with an average particle size of 80 nm, and then placed in a hot press furnace and sintered at 1950°C and 40 MPa to obtain a β-SiC sintered body.

[0079] Example 3

[0080] This embodiment provides a method for preparing a high-purity, low-resistivity β-phase silicon carbide material.

[0081] The preparation method specifically comprises the following steps:

[0082] (1) Rice husks and deionized water are mixed in a volume ratio of 1:2, and after being fully stirred, the upper layer of rice husks is taken out and soaked in a weakly acidic sulfuric acid aqueous solution for later use; before use, the upper layer of rice husks is boiled in the sulfuric acid aqueous solution for 5 times, repeatedly washed with distilled water, and then dried.

[0083] (2) The rice husk obtained by drying in step (1) is placed in a heating furnace, kept at 450° C. for 6 h in a low oxygen environment, taken out after cooling in the furnace, and placed in a ball mill at a speed of 200 r / min for 1 h to obtain carbonized rice husk powder; the carbonized rice husk powder A under the sieve is taken out and set aside.

[0084] (3) The carbonized rice husk powder A obtained in step (2) and a 15 wt % ammonia solution are heated in a water bath at 100° C. and stirred for 2 h. The filtrate obtained by filtering is a silicate aqueous solution B for later use. The filter residue D obtained by drying is later use.

[0085] (4) The filter residue D obtained in step (3) is placed in a vacuum furnace and kept at 650° C. for 3 h in vacuum. After cooling in the furnace, the residue is taken out and washed until neutral to obtain rice husk carbon E, which is then dried for later use.

[0086] (5) The silicate aqueous solution B obtained in step (3) and the rice husk carbon E obtained in step (4) are mixed according to a molar ratio of carbon to silicon of 2.3, placed in a ball mill and ball milled at a speed of 150 r / min for 2 h, and then taken out and placed in a vacuum oven to dry to constant weight to obtain a loose block F.

[0087] (6) The loose block F obtained in step (5) is placed in a vacuum furnace and slowly calcined at 1800° C. to obtain β-SiC powder.

[0088] (7) The β-SiC powder obtained in step (6) is mixed with 25 wt.% of ultrafine silicon carbide powder with an average particle size of 30 nm, and the mixture is placed in a hot press furnace and sintered at 1900° C. and 48 MPa to obtain a β-SiC sintered body.

[0089] Comparative Example

[0090] Comparative Example 1

[0091] This comparative example provides a method for preparing a high-purity, low-resistivity β-phase silicon carbide material. The difference between this comparative example and Example 1 is that in step (1), the rice husk is directly soaked in deionized water instead of being soaked in a weakly acidic hydrochloric acid aqueous solution. The rest is consistent with Example 1.

[0092] Comparative Example 2

[0093] This comparative example provides a method for preparing a high-purity, low-resistivity β-phase silicon carbide material. The difference between this comparative example and Example 1 is that in step (1), the rice husks are directly washed and dried after being soaked in a weakly acidic hydrochloric acid aqueous solution, and the spare rice husks are not placed in a dilute hydrochloric acid aqueous solution for boiling and then washed with water. The rest is consistent with Example 1.

[0094] Comparative Example 3

[0095] This comparative example provides a method for preparing a high-purity, low-resistivity β-phase silicon carbide material. The difference between this comparative example and Example 1 is that the weakly acidic aqueous solution used in step (1) and the acid added to the acidic aqueous solution are both acetic acid. The rest is consistent with Example 1.

[0096] Comparative Example 4

[0097] This comparative example provides a method for preparing a high-purity, low-resistivity β-phase silicon carbide material. The difference between this comparative example and Example 1 is that the sieve used in step (2) is a metal standard sieve of the same mesh number. The rest is consistent with Example 1.

[0098] Comparative Example 5

[0099] This comparative example provides a method for preparing a high-purity, low-resistivity β-phase silicon carbide material. The difference between this comparative example and Example 1 is that the alkali used in step (3) is sodium hydroxide. The rest is consistent with Example 1.

[0100] Comparative Example 6

[0101] This comparative example provides a method for preparing a high-purity, low-resistivity β-phase silicon carbide material. The difference between this comparative example and Example 1 is that the alkali used in step (3) is potassium hydroxide, and no nitrogen element is introduced; and in step (7), sintering is completed in a hot press furnace in a nitrogen atmosphere. The rest is consistent with Example 1.

[0102] Performance test results

[0103] (I) Crystal form detection

[0104] The crystal form of the β-SiC sintered body obtained in Example 1 above was detected.

[0105] The detection method is as follows:

[0106] Sample preparation: The sintered body should be flat and smooth with a thickness of 1-5mm and a length and width of 15mm. The synthetic powder should pass through a 320-mesh sieve and have a mass of >5g.

[0107] X-ray diffractometer (XRD) was used to analyze the phase composition of SiC sintered body and synthetic powder. The radiation source of the diffractometer was CuK target, the wavelength was 1.5406A, and the 2θ angle was between 20° and 80°.

[0108] Test results such as Figure 1 As shown, (a) is the result of the SiC sintered body obtained in step (7), and (b) is the result of the SiC powder obtained in step (6). Figure 1 The test results are compared with those of the standard PDF card. In both cases, SiC is the only crystalline phase and exists in the form of β phase (3C).

[0109] (II) The metal ion content, purity and resistivity of the β-SiC sintered bodies obtained in the above-mentioned embodiments and comparative examples were tested respectively. The testing method is as follows:

[0110] (1) Purity and metal ion content: Glow discharge mass spectrometry (GDMS) is used to test and analyze the elemental composition and content of the obtained block. The sample size is not less than 20*20*10 mm.

[0111] (2) Resistivity: The volume resistivity (unit: Ω·cm) of the obtained block was tested using a four-probe resistivity tester, where the sample thickness was measured using a vernier caliper / micrometer.

[0112] The test results are shown in Table 1.

[0113] Table 1 Test results of the above examples and comparative examples

[0114]

[0115]

[0116] As shown in Table 1, the purity of the β-SiC sintered bodies obtained in Examples 1-3 is higher than 99.99%, and the highest can reach 99.999%; the overall content of metal ions is low; the volume resistivity is ≤0.5Ω·cm, and the lowest can reach 10 -3 Ω·cm. However, in Comparative Examples 1-3, due to inadequate acid washing and water washing processes, the metal impurities in the rice husk composition were not completely removed, resulting in a high content of some impurities and a reduced purity; in Comparative Example 4, a metal standard sieve was used in the production process, resulting in a high content of metal impurities and a low purity; in Comparative Example 5, sodium hydroxide was used as an alkali, resulting in an excessively high sodium ion content, and no nitrogen element was involved in the synthesis reaction, resulting in a high resistivity; in Comparative Example 6, nitrogen was not introduced in the powder synthesis stage, and only a nitrogen atmosphere was used in the final hot pressing sintering stage, but the resistivity was still higher than 1Ω·cm.

[0117] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing high-purity, low-resistivity β-phase silicon carbide material, characterized in that: The preparation method specifically comprises the following steps: (1) Mix rice husks and water in a volume ratio of 1:(1-5), stir thoroughly, take out the upper layer of rice husks and place them in a weakly acidic aqueous solution for later use; before use, boil the rice husks in the acidic aqueous solution for 2-5 times, wash and dry; (2) placing the dried rice husk in a low oxygen environment at 450-600° C. for 1-6 hours, and after cooling, ball milling at a speed of 100-200 r / min for 1-4 hours to obtain carbonized rice husk powder; passing through a 150-300 mesh fine sieve, and retaining the carbonized rice husk powder A on the sieve; (3) heating the carbonized rice husk powder A and a 10-50 wt% alkali aqueous solution in a water bath at 90-100° C. for 2-4 hours with stirring, and filtering; the resulting filtrate is a silicate aqueous solution B; and drying the resulting filter residue D; (4) placing the filter residue D at 600-800° C. in vacuum or under inert gas protection for 1-3 hours, cooling and washing to neutrality to obtain rice husk carbon E, and drying; (5) The silicate aqueous solution B and the rice husk carbon E are mixed according to a molar ratio of carbon to silicon of 2.3-2.5, ball-milled at a speed of 100-200 r / min for 1-2 h, and dried to constant weight to obtain a loose block F; (6) slowly calcining the loose block F at 1500-1850° C. to obtain β-SiC powder; (7) The β-SiC powder is mixed with 1-30 wt.% of ultrafine silicon carbide powder with an average particle size of 10-100 nm, and sintered at 1900-2000° C. and 30-50 MPa to obtain a β-SiC sintered body.

2. The preparation method according to claim 1, characterized in that: The purity of the β-SiC sintered body is higher than 99.99% and the volume resistivity is ≤0.5Ω·cm.

3. The preparation method according to claim 1, characterized in that: In step (1), the weakly acidic aqueous solution and the acid in the acidic aqueous solution are inorganic acids.

4. The preparation method according to claim 1, characterized in that: The acid in the weakly acidic aqueous solution and the acidic aqueous solution is at least one of hydrochloric acid, sulfuric acid, nitric acid and acetic acid.

5. The preparation method according to claim 1, characterized in that: In step (2), the material of the fine sieve is an organic material and does not contain metal elements.

6. The preparation method according to claim 5, characterized in that: The material of the fine sieve is plastic material.

7. The preparation method according to claim 1, characterized in that: In step (3), the alkali in the alkaline aqueous solution is at least one of ammonia water and an organic base, and the purity of the alkali is higher than 99% and does not contain any metal elements.

8. The preparation method according to claim 7, characterized in that: The alkali in the alkaline aqueous solution must contain nitrogen element.

9. A high-purity, low-resistivity β-phase silicon carbide material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the high-purity, low-resistivity β-phase silicon carbide material according to claim 9 as a component material for semiconductor manufacturing.

Citation Information

Patent Citations

  • Method for producing porous nano silica and active carbon by utilizing rice hull ash

    CN101920966A

  • A method of preparing a porous silicon carbide material based on rice hulls

    CN106395787A

  • Composition and method for making silicon-containing products

    US20060089258A1

  • Method for producing solar cell-grade silicon from rice hulls

    US4214920A

  • Materials from rice hull ash

    WO2012166728A1

Cited By

  • Sodium-ion battery negative electrode material as well as preparation method and application thereof

    CN122212097A

  • Sodium-ion battery negative electrode material and preparation method and application thereof

    CN122212097B